Analysis on the opinions of employees working in provincial directorates of youth and sports regarding six sigma management model - Yücel, Ali Serdar; Karataş, Özgür (Horizon Research Publishing, 2019)
The purpose of this study is to evaluate the opinions of those working in Provincial Directorates of Youth and Sports – serving as the field service within the body of General Directorate of Sports affiliated to the Ministry of Youth and Sports in Turkey – regarding the applicability of Six Sigma management model by some variables. "Descriptive Survey Model" was used in this research. The research population is composed of the employees working in Provincial Directorates of Youth and Sports in Turkey and the sample is composed of randomly selected 210 employees among those actively working in these directorates. A questionnaire was applied in obtaining the research data. It has been determined in the research that the opinions of the participants on the applicability of Six Sigma management model are positive, a quality management model isn't applied in provincial directorates, quality education isn't addressed sufficiently and there isn't any quality department or the personnel recruited in this department. In conclusion, it has been established that employee opinions on the applicability of Six Sigma management model in Provincial Directorates of Youth and Sports are positive and they constitute a basis for the applicability of Six Sigma management model when the research results are addressed by taking into account the fact that ensuring the leadership and support of top management in addition to the principles of Six sigma management model, such as Customer orientation, Tolerance for failure, Process-oriented Management and Continuous Development. Active Participation of Everyone and Tolerance for Failure are two of the highly important steps of "Six Sigma" applications. © 2019 by authors, all rights reserved.
Keywords: Product; Quality; Six Sigma; Sports; Youth